2003
DOI: 10.1080/14034940210164920
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence - stability over time and relation to health, disease, and psychosocial changes in a general population: A longitudinal study

Abstract: We found that SOC was only stable for those with initially high levels of SOC. For other people, individual conditions and societal changes influenced their SOC. Further longitudinal studies in normal populations are needed to investigate the stability of SOC scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
3
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(162 citation statements)
references
References 28 publications
14
138
3
7
Order By: Relevance
“…Antonovsky (1987) hypothesized that SOC develops during childhood and stabilizes during the early adulthood stage. In contrast, other research proposed SOCs changes over an entire lifetime (e.g., Nilsson, Holmgren, Stegmayr, & Westman, 2003;Nilsson, Leppert, Simonsson, & Starrin, 2010). These findings raise several important issues regarding the longitudinal fluctuations as well as stability versus flexibility in individual SOC across the different development phases.…”
Section: Flexibility Versus Stabilitycontrasting
confidence: 45%
“…Antonovsky (1987) hypothesized that SOC develops during childhood and stabilizes during the early adulthood stage. In contrast, other research proposed SOCs changes over an entire lifetime (e.g., Nilsson, Holmgren, Stegmayr, & Westman, 2003;Nilsson, Leppert, Simonsson, & Starrin, 2010). These findings raise several important issues regarding the longitudinal fluctuations as well as stability versus flexibility in individual SOC across the different development phases.…”
Section: Flexibility Versus Stabilitycontrasting
confidence: 45%
“…The current study used the 13-item version of the Sense of Coherence Scale (SOC) and included the sum score of all items in the analysis (Cronbach's alpha = 0.82) (Antonovsky 1993;Schnyder et al 2000;Schumacher et al 2000;Nilsson et al 2003).…”
Section: Person Variablesmentioning
confidence: 99%
“…Test-retest correlations have shown a stability ranging from .69 to .78 (1 year), .64 (3 years), .42 to .45 (4 years), .59 to .67 (5 years) to .54 (10 years) (Antonovsky, 1993). The present 2-year coefficient of .72 can also be compared with Swedish data from a 5-year stability study in a general population aged 25-74 years, where Nilsson, Holmgren, Stegmayr and Westman (2003) reported a Pearson correlation coefficient of .57 (p<0.01). For the other scales tested in our study, only short-term based test-retest correlation coefficients have been reported; for self-esteem a coefficient of .85 was reported from a test of 28 students over a 2-week interval (Bowling, 2001) and for depression, correlation coefficients ranged from .51-.59 depending on length of time passed (from 2 weeks up to 8 weeks) (Radloff, 1977).…”
Section: Stability Over 2 Yearsmentioning
confidence: 65%
“…Our data correspond well with results from previous studies. For sense of coherence, we noted Cronbach's alpha to .82-.84, while Nilsson et al (2003) reported an alpha of .79 at baseline and .81 at follow-up. In a review of 5 published studies using the SOC 13-instrument, Antonovsky ((1993) reported an average alpha of .82 (range .74-.91).…”
Section: Reliability and Measurement Errormentioning
confidence: 99%